Pancreatic Metastasis from Malignant Melanoma: Not All That Glitters Is Gold - Vargas-Jiménez, Jose (Case Rep Gastroenterol, 2021)
Pancreatic adenocarcinoma is the most common malignancy of the pancreas; on rare occasions, metastatic tumors are present. Differentiating a primary neoplasm from a metastatic one is important for ensuring adequate treatment for the patient. We present a case of metastatic melanoma to the pancreas. A 60-year-old man presented with a history of weight loss, vague abdominal pain, jaundice, and pruritus. Laboratory tests showed increased total bilirubin, with a direct fraction predominance, as well as increased alkaline phosphatase and gamma glutamyl transferase. Imaging studies revealed a mass in the head of the pancreas. Endoscopic ultrasound (EUS)-guided fine needle biopsy was performed, and histologic examination confirmed the diagnosis of metastatic melanoma. This case report illustrates the invaluable use of EUS-guided tissue acquisition in the study of pancreatic solid lesions to obtain an accurate diagnosis. Melanomas should always be part of a differential diagnosis when evaluating patients with pancreatic masses.